A PLAG1 mutation contributed to stature recovery in modern cattle - Utsunomiya, Yuri Tani [UNESP]; Milanesi, Marco [UNESP]; Utsunomiya, Adam Taiti Harth [UNESP]; Torrecilha, Rafaela Beatriz Pintor [UNESP]; Kim, Eui-Soo; Costa, Márcio Silva; Aguiar, Tamíris Sayuri [UNESP]; Schroeder, Steven; Do Carmo, Adriana Santana; Carvalheiro, Roberto [UNESP]; Neves, Haroldo Henrique Rezende; Padula, Romulo Cláudio Morozini; et al. (Springer Nature, 2017)
The recent evolution of cattle is marked by fluctuations in body size. Height in the Bos taurus lineage was reduced by a factor of ∼1.5 from the Neolithic to the Middle Ages, and increased again only during the Early Modern Ages. Using haplotype analysis, we found evidence that the bovine PLAG1 mutation (Q) with major effects on body size, weight and reproduction is a >1,000 years old derived allele that increased rapidly in frequency in Northwestern European B. taurus between the 16th and 18th centuries. Towards the 19th and 20th centuries, Q was introgressed into non-European B. taurus and Bos indicus breeds. These data implicate a major role of Q in recent changes in body size in modern cattle, and represent one of the first examples of a genomic sweep in livestock that was driven by selection on a complex trait.